Breadcrust Bomb Merapi: Geological-Inspired Culinary Art and Socio-Cultural Empowerment in Merapi Region - Dina Tania; Herry Riswandi (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article explores the creation of Breadcrust Bomb Merapi, a culinary art inspired by the geological features of Mount Merapi in Yogyakarta, Indonesia. The study aims to promote socio-cultural empowerment and geology education while supporting local communities surrounding Mount Merapi. The research methodology involved direct interviews with residents of the South Slope of Mount Merapi to identify the most popular products among tourists and the feasibility of their development. The selection process led to the production of Breadcrust Bomb Merapi, a cake resembling the explosive eruptions of Merapi, featuring a crust-like texture with a soft interior filled with melted cheese, symbolizing hot lava. The legal aspects of the creation were ensured through copyright registration. The results demonstrate the successful integration of geological inspiration into culinary art, providing a unique Merapi culinary experience for visitors and offering socio-cultural and economic opportunities for the local community. The implication of this study lies in its contribution to geotourism, ecotourism, and the preservation of local cultural heritage while fostering socio-economic development in the Merapi region. Highlight: Natural beauty and geological evolution of Mount Merapi Breadcrust Bomb Merapi: Culinary art inspired by explosive eruptions Socio-cultural empowerment through local culinary development Keyword: Mount Merapi, Breadcrust Bomb Merapi, Geology-Inspired Culinary Art, Socio-Cultural Empowerment, Tourism